The Sustainable Service Management Factors in High Technology Transport Service Industry - Abdullah, M.A.; Chew, B.C.; Hamid, S.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Recently, environmental sustainability has become a global concern and the majority of world organizations are striving hard to achieve this mission. Despite, many studies have attempted to explore the factors that help towards environmental sustainability in the manufacturing sector, the service sector has not yet received a considerable attention in all countries generally and in developing countries particularly. Thus, this paper aims to explore the factors that help to attain environmental sustainability in the service sector. A case study through fifteen semi-structured interviews is conducted with managers from AirAsia as the High Technology Transport Service Provider to explore the factors that are related to environmental sustainability and green services. The finding of this paper emphasizes to three important factors namely top management support, ensure quality control and organizational capabilities towards sustainable services on green practices rather than the economic gain on profit maximization alone.